Biocatalytic conversion of a lactose-rich dairy waste into D-tagatose, D-arabitol and galactitol using sequential whole cell and fermentation technologies. (August 2022) - Zhang, Guoyan; Zabed, Hossain M.; An, Yingfeng; Yun, Junhua; Huang, Jiaqi; Zhang, Yufei; Li, Xiaolan; Wang, Jiangfei; Ravikumar, Yuvaraj; Qi, Xianghui
Graphical abstract: Highlights: Cheese whey powder (CWP) was used to produce three value-added rare sugars. D-tagatose was produced by feeding CWP during whole cell biotransformation with E. coli . D-arabitol and galactitol were produced from residual sugars by fermentation with yeast. Finally, 68.35 g/L D-tagatose, 60.12 g/L D-arabitol and 28.26 g/L galactitol were produced. The net titer of the three value-added products was 156.73 g/L. Abstract: Dairy industry waste has been explored as a cheap and attractive raw material to produce various commercially important rare sugars. In this study, a lactose-rich dairy byproduct, namely cheese whey powder (CWP), was microbially converted into three low caloric sweeteners using whole-cell and fermentation technologies. Firstly, the simultaneous lactose hydrolysis and isomerization of lactose-derived D-galactose into D-tagatose was performed by an engineered Escherichia coli strain co-expressing β-galactosidase and L-arabinose isomerase, which eventually produced 68.35 g/L D-tagatose during sequential feeding of CWP. Subsequently, the mixed syrup containing lactose-derived D-glucose and residual D-galactose was subjected to fermentation by Metschnikowia pulcherrima E1, which produced 60.12 g/L D-arabitol and 28.26 g/L galactitol. The net titer of the three rare sugars was 156.73 g/L from 300 g/L lactose (equivalent to 428.57 g/L CWP), which was equivalent to 1.12 mol product/mol lactose and 52.24% conversion efficiency in terms of lactose.